Determination of Physical and Nutritional Quality of Silages Prepared from Three Different Species of Fodder (South Asian Journal of Agriculture, 2025)
Livestock production is often limited by the availability of high-quality forage. Most of the fodders and grasses are grown seasonally and are particularly scarce during the dry season. Silage making is a good technology for fodder conservation to ensure green fodders for livestock throughout the year. This study was carried out to observe the efficiency of small-scale silage production using simple low-cost technology and to ascertain the nutritional value of the silage. Cultivation of fodder species and preparation of silage were carried out in the field laboratory of Agrotechnology Discipline, Khulna University.  The fodder for making silage was cut into 2 to 3 cm pieces, packed in plastic bags, carefully sealed and stored in drums with adequate sealing for 60 days. Three fodder species viz. oat (Avena sativa L.), maize (Zea mays L.) and sorghum (Sorghum bicolour L.) were selected for silage preparation. Three replicates were maintained for each species. To determine the physical characteristics of silages; color, aroma, texture and presence/absence of fungi were examined. Chemical analysis was performed in the animal husbandry laboratory, at Khulna University. Statistical analysis was carried out using the SPSS (version 22) computer program. It was found that color, odor and texture of silages were acceptable in all the samples and no fungus was observed in any of the samples. Chemical analysis showed the highest dry matter (DM) content (g 100g-1) in sorghum silage (22.72±0.88) and the lowest in maize silage (13.64±0.69) (p